Two remarks on variants of simple eco-grammar systems - Csima, Judit (Acta Cybernetica, 2000)
Two powerful variants of simple eco-grammar systems, namely extended tabled simple eco-grammar systems (ETEG systems) and weak extended simple eco-grammar systems (wEEG systems) are studied. It is proved that both modifications of the original definition result in universal power: all recursively enumerable languages can be obtained both by ETEG and by wEEG systems.